Political Renewal of Copyright Protection Law in the Problem of Copyright Infringement (Multi-Dimensional Law Narrative) - Melki Suhery Simamora; Prihartono Prihartono (Jurnal Akta, 2021)
Copyright is a high reality of various values, including economic value, this is because copyright that is born from copyright, taste, and intention is able to color the development of human life through objects born from the copyright process. But in its development various copyrights are not noticed in this country. The rise of piracy of song copyrights, for example, can only be economically profitable for the perpetrators of song copyright piracy, while not many creators can seek justice for it. This is increasingly unfair with Article 112 to Article 119 of Act No. 28 of 2014 changing a copyright offense into a complaint offense which further marginalizes the rights of the creator of a copyrighted work in this country. Therefore, it is necessary to have a joint discussion regarding the development of legal politics of creator protection related to copyright offenses that occur. Relevant updates can be made through changes to the complaint offense in theInvite-Act No. 28 of 2014 becomes a general criminal offense. So it is hoped that criminal offenses against copyright can be handled without having to complain from the copyright owner first so that copyright protection can be optimally implemented, this will be able to improve civilization for the better due to the protection of the economic aspect of copyright through criminal sanctions imposed firm.